A Development Of Solar-Powered Greenped As A Complex Security Vehicle - M. atta alhafizht; Muhammad nurhasan; M. rangga artiman; M. shafarizky; Solly Aryza (Sean Institute, 2025)
The development of solar-powered vehicles offers a sustainable and innovative solution for energy-efficient transportation systems. This study focuses on designing and analyzing the GreenPed, a solar-powered complex security vehicle, to enhance operational efficiency and reduce environmental impact. The GreenPed integrates renewable energy technologies with advanced security systems, making it a versatile and eco-friendly solution for security operations in various environments. The research includes the design of a photovoltaic system to optimize energy capture and storage, ensuring sufficient power supply for both vehicle propulsion and security equipment. Key components such as solar panels, energy storage systems, and electric motors are selected based on their performance and reliability. The vehicle is also equipped with modern surveillance tools, including cameras, motion detectors, and real-time communication systems, powered by the onboard solar energy system. Simulation and testing results demonstrate the feasibility of the GreenPed in maintaining consistent performance under diverse environmental conditions. The analysis highlights significant reductions in operational costs and carbon emissions compared to traditional security vehicles. Moreover, the integration of solar technology enhances the vehicle's autonomy, eliminating the dependence on external charging infrastructure. This research concludes that the GreenPed represents a viable and sustainable solution for security operations, providing both environmental and operational benefits. It sets a benchmark for the adoption of renewable energy technologies in specialized vehicles.